2006
DOI: 10.3917/spub.064.0513
|View full text |Cite
|
Sign up to set email alerts
|

Comparaison du score individuel de précarité des Centres d'examens de santé, EPICES, à la définition socio-administrative de la précarité

Abstract: In French Health Examination Centres, populations in deprived situation were usually defined by administrative criteria The aim of the study was to investigate whether EPICES, a new individual index of deprivation, was more strongly related to health status than an administrative classification. The EPICES score was calculated on the basis of 11 weighted questions related to material and social deprivation. Participants were 197, 389 men and women, aged over 18, encountered in 2002 in French Health Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 13 publications
1
40
0
6
Order By: Relevance
“…Nonetheless, the results show that this ratio is associated with a higher risk of death (hazard ratio 1.34, 95% CI 1.25-1.44; p < 0.0001), which is an argument in favor of the reliability of this measure [29]. Several authors have underlined the importance of taking into account health insurance in psychosocioeconomic precariousness measure [19,30] as well as health behaviors [31]. Unfortunately, this information has not been collected in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the results show that this ratio is associated with a higher risk of death (hazard ratio 1.34, 95% CI 1.25-1.44; p < 0.0001), which is an argument in favor of the reliability of this measure [29]. Several authors have underlined the importance of taking into account health insurance in psychosocioeconomic precariousness measure [19,30] as well as health behaviors [31]. Unfortunately, this information has not been collected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, Lee et al [18] reported a cumulative socioeconomic risk for cognitive impairment in elderly. In line with this cumulative approach, we meant to focus on the association between multiple vulnerabilities (the concept of ‘psychosocioeconomic precariousness') and cognitive ageing, using psychosocial variables in addition to occupation, education and income, as it has been recently proposed [19,20]. Therefore, the novelty of this research is that we combined a cumulative approach of precariousness (each item is scored 1 point and considered as providing additional precariousness) with a multidimensionality definition of precariousness including indicators of poor socioeconomic status and psychosocial vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le score EPICES va de 0 (absence de précarité) à 100 (maximum de précarité), le seuil de précarité étant de 30 [30]. Plusieurs publications ont montré que ce score est significativement lié à de très nombreux indicateurs de santé avec « relations score dépendantes » : comportements à risque, non recours aux soins, mauvaise santé perçue et santé mesurée [30,[33][34][35]. Il est également lié au diabète et à ses complications [36], au syndrome métabolique [37] et aux indicateurs de santé mentale [38,39].…”
Section: Résultatsunclassified